The Potential of Mount Lakus for Sustainable Municipal Development in Bobonaro, Timor-Leste - Gabriel, Carlito; Ximenes, João (Yayasan Nurul Musthafa, 2025)
Mountain conservation in Timor-Leste plays a crucial role in maintaining water resources, preserving biodiversity, and preventing natural disasters. Such conservation efforts directly contribute to improving the quality of life of both humans and wildlife, as well as enhancing community well-being. Mount Lakus, located at the intersection of several villages in Bobonaro Municipality, holds ecological, cultural, and economic significance for the local population. This study employed a descriptive survey method through field observations and literature review to assess the potential of Mount Lakus for sustainable municipal development. The findings show that the conservation of Mount Lakus could support tourism, agriculture, and environmental protection, while also generating socio-economic benefits for local communities. Establishing Mount Lakus as a National Park would not only preserve natural resources for present and future generations but also promote job creation, support small and medium enterprises, and attract green investment. Therefore, collaborative action between government, local communities, and stakeholders is required to ensure that Mount Lakus contributes effectively to sustainable development in Bobonaro and Timor-Leste as a whole. [Konservasi gunung di Timor-Leste memainkan peran penting dalam menjaga sumber daya air, melestarikan keanekaragaman hayati, dan mencegah bencana alam. Upaya konservasi tersebut secara langsung berkontribusi pada peningkatan kualitas hidup manusia dan satwa liar, serta meningkatkan kesejahteraan masyarakat. Gunung Lakus, yang terletak di pertemuan beberapa desa di Kabupaten Bobonaro, memiliki nilai ekologis, budaya, dan ekonomi yang signifikan bagi masyarakat setempat. Penelitian ini menggunakan metode survei deskriptif melalui observasi lapangan dan kajian literatur untuk menilai potensi Gunung Lakus dalam pembangunan daerah berkelanjutan. Hasil penelitian menunjukkan bahwa konservasi Gunung Lakus dapat mendukung sektor pariwisata, pertanian, dan perlindungan lingkungan, sekaligus menghasilkan manfaat sosial-ekonomi bagi masyarakat lokal. Penetapan Gunung Lakus sebagai Taman Nasional tidak hanya akan melestarikan sumber daya alam bagi generasi sekarang dan mendatang, tetapi juga mendorong penciptaan lapangan kerja, mendukung usaha kecil dan menengah, serta menarik investasi hijau. Oleh karena itu, diperlukan kerja sama antara pemerintah, masyarakat lokal, dan para pemangku kepentingan untuk memastikan Gunung Lakus dapat memberikan kontribusi nyata bagi pembangunan berkelanjutan di Bobonaro dan Timor-Leste secara keseluruhan.]